2018
DOI: 10.7554/elife.32893
|View full text |Cite
|
Sign up to set email alerts
|

IRS-1 acts as an endocytic regulator of IGF-I receptor to facilitate sustained IGF signaling

Abstract: Insulin-like growth factor-I receptor (IGF-IR) preferentially regulates the long-term IGF activities including growth and metabolism. Kinetics of ligand-dependent IGF-IR endocytosis determines how IGF induces such downstream signaling outputs. Here, we find that the insulin receptor substrate (IRS)−1 modulates how long ligand-activated IGF-IR remains at the cell surface before undergoing endocytosis in mammalian cells. IRS-1 interacts with the clathrin adaptor complex AP2. IRS-1, but not an AP2-binding-deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 80 publications
2
34
0
Order By: Relevance
“…The molecular basis for the close interactions between IGF-IR endocytosis and its signaling components is still poorly understood. Recently, it has been suggested that the ability of insulin receptor substrate-1 (IRS-1) to interact with the clathrin adapter protein AP2, which is essential for endocytosis, plays an important role in IGF-IR internalization [28]. Overexpression of IRS-I resulted in the accumulation of activated IGF-IR at the cellular membrane [28].…”
Section: The Igf-ir and Endocytosismentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular basis for the close interactions between IGF-IR endocytosis and its signaling components is still poorly understood. Recently, it has been suggested that the ability of insulin receptor substrate-1 (IRS-1) to interact with the clathrin adapter protein AP2, which is essential for endocytosis, plays an important role in IGF-IR internalization [28]. Overexpression of IRS-I resulted in the accumulation of activated IGF-IR at the cellular membrane [28].…”
Section: The Igf-ir and Endocytosismentioning
confidence: 99%
“…Recently, it has been suggested that the ability of insulin receptor substrate-1 (IRS-1) to interact with the clathrin adapter protein AP2, which is essential for endocytosis, plays an important role in IGF-IR internalization [28]. Overexpression of IRS-I resulted in the accumulation of activated IGF-IR at the cellular membrane [28]. Conversely, knockdown of IRS-I induced faster internalization of IGF-IRs [28].…”
Section: The Igf-ir and Endocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…These results can explain why the activated IR is preferentially internalized. IRS1 interacts with the adaptor related protein complex 1 Mu 1 subunit (AP1M1) and AP2M1 through multiple YXXΦ (X, any amino acids; Φ, bulky hydrophobic residues) motifs 46,47 .…”
Section: Irs1/2 Promote Ir Endocytosis Insulin Binding To Ir Promotementioning
confidence: 99%
“…The IRS1-AP2M1 interaction negatively regulates endocytosis of insulin-like growth factor 1 receptor (IGF1R) 47 . We confirmed that in vitro translated Myc-IRS1 full-length and the YXXΦcontaining central region (residues 449-679) bound to GST-AP2M1 ( Fig.…”
Section: Irs1/2 Promote Ir Endocytosis Insulin Binding To Ir Promotementioning
confidence: 99%